HPLC/MS identification of the polyphenols present in an extract of Myrtus communis L. obtained by supercritical fluid extraction - Paula Pereira (Journal Biomedical and Biopharmaceutical Research (BBR), 2017)
In this work, we studied an extract obtained by supercritical fluid extraction (SFE) using a simpler method of cosolvent (ethanol) addition. Instead of using a liquid pump, which is the most common process, the ethanol was directly introduced in the extraction cell, immediately after loading the cell with the plant sample. it was our intent to investigate if this change would have any effect in the composition of the extract obtained. The experimental conditions used were: temperature 48° C, pressure 10 MPa, supercritical fluid (SCF) flow rate 130.71dm3h-1 (0.238 kgh-1) and an ethanol volume of 104 cm3. The composition of the extract obtained was different from previous tests, and the compounds identified by HPLC-MS were quinic acid, quinic acid 3,5-di-O-gallate, quinic acid 3,4,5-galloyl, myricetin-galactoside gallate, quercetin-galactoside gallate, quercetin, and myricetin-galactosiderhamnoside.